Humans and great apes share increased neocortical neuropeptide Y innervation compared to other haplorhine primates - Raghanti, Mary Ann; Edler, Melissa K.; Meindl, Richard S.; Sudduth, Jessica; Bohush, Tatiana; Erwin, Joseph M.; Stimpson, Cheryl D.; Hof, Patrick R.; Sherwood, Chet C. (Frontiers in Human Neuroscience, 2014)
Neuropeptide Y (NPY) plays a role in a variety of basic physiological functions and has also been implicated in regulating cognition, including learning and memory. A decrease in neocortical NPY has been reported for Alzheimer’s disease, schizophrenia, bipolar disorder, and depression, potentially contributing to associated cognitive deficits. The goal of the present analysis was to examine variation in neocortical NPY-immunoreactive axon and varicosity density among haplorhine primates (monkeys, apes, and humans). Stereologic methods were used to measure the ratios of NPY-expressing axon length density to total neuron density (ALv/Nv) and NPY-immunoreactive varicosity density to neuron density (Vv/Nv), as well as the mean varicosity spacing in neocortical areas 10, 24, 44, and 22 (Tpt) of humans, African great apes, New World monkeys, and Old World monkeys. Humans and great apes showed increased cortical NPY innervation relative to monkey species for ALv/Nv and Vv/Nv. Furthermore, humans and great apes displayed a conserved pattern of varicosity spacing across cortical areas and layers, with no differences between cortical layers or among cortical areas. These phylogenetic differences may be related to shared life history variables and may reflect specific cognitive abilities.